Thermo-fluidic transport of electromagnetohydrodynamic flow of sodium alginate based Casson nano fluid passing through a porous microtube under the effect of streaming potential - Reza, Motahar; Rana, Amalendu (International Journal of Engineering and Technology, 2021)
Thermal transport characteristics of Casson nanofluid through a porous microtube is analyzed under the effect of streaming potential and constant pressure gradient with electrokinetic effect associated with applied magnetic field. An analytical solution of the velocity and temperature distribution of Casson-nano fluid through the porous microtube related to combining effects of electromagnetohydrodynamics forces under the effect of streaming potential have been obtained. The significant influences of various non-dimensional parameters on velocity and temperature profiles are discussed in this study. Also, it is revealed the impact of nano particles on flow transport and heat transfer phenomenon. Furthermore, the Nusselt number is calculated analytically. The variations of pertinent parameters such as Hartmann number, Darcy number,Casson parameter, volume friction parameter of nanoparticles, joule heating parameter are delineated graphically and discussed in details.Â Â